: № 147 (2278) (1984)
Титульного листа нет, описание составлено по обложке Для служебного пользования, экз. № 102 Экземпляры: УКП (20241118) / Инвентарный номер: АП19840205 / Сис.шифр: 65.32 / Авт.знак: И 93 / ГРНТИ: 68 / ББК: 65.32(2Рос.Удм)